Magia e tecnologia a serviço da verdade: O Senhor dos Anéis e a crítica à modernidade - Teixeira, Paulo Armando Cristelli (2011)
The present study aims to discuss and question the images in the book ―The Lord of the Rings‖, from the British author JRR Tolkien, especially with regard to issues of modernity and modernization in England in the first half of the XX century. The images and representations contained in the work are analyzed by the author's anti-technology position, within his historical context, where the machine is used to build an important role in building a positive image of modernity. As sources of this research, we use the author´s exchanged letters, the literary trilogy and some war paintings produced during the Second World War